Delayed MSC therapy enhances resolution of organized pneumonia induced by antibiotic resistant Klebsiella pneumoniae infection - Byrnes, Declan; Masterson, Claire; Brady, Jack; Horie, Shahd; McCarthy, Sean D.; Gonzalez, Hector; O’Toole, Daniel; Laffey, John (Frontiers in Medicine, 2023)
Introduction: Mesenchymal stromal cells (MSC) are a promising therapeutic for pneumonia-induced sepsis. Here we sought to determine the efficacy of delayed administration of naïve and activated bone marrow (BM), adipose (AD) and umbilical cord (UC) derived MSCs in organized antibiotic resistant Klebsiella pneumosepsis. Methods: Human BM-, AD- and UC-MSCs were isolated and expanded and used either in the naïve state or following cytokine pre-activation. The effect of MSC tissue source and activation status was assessed first in vitro. Subsequent experiments assessed therapeutic potential as a delayed therapy at 48hrs post infection of rodents with Klebsiella pneumoniae, with efficacy assessed at 120hrs. Results: BM-, AD- and UC-MSCs accelerated epithelial healing, increased phagocytosis, and reduced ROS-induced epithelial injury in vitro, with AD-MSCs less effective, and naïve MSCs more effective than pre-activated MSCs. Delayed MSC administration in pre-clinical organized Klebsiella pneumosepsis had no effect on physiologic indices, but enhanced resolution of structural lung injury. Delayed therapy with pre-activated MSCs reduced mRNA concentrations of fibrotic factors. Naïve MSC treatment reduced key circulating cell proportions and increased bacterial killing capacity in the lungs whereas pre-activated MSCs enhanced the phagocytic index of pulmonary white cells. Discussion: Delayed MSC therapy enhanced resolution of lung injury induced by antibiotic resistant Klebsiella infection and favorably modulated immune cell profile. Overall, AD-MSCs were less effective than either UC- or BM-MSCs, while naïve MSCs had a more favorable effect profile compared to pre-activated MSCs.